Discriminatory Value of Adiponectin to Leptin Ratio for COVID-19 Pneumonia. (26th April 2022) - Tonon, Federica; Di Bella, Stefano; Giudici, Fabiola; Zerbato, Verena; Segat, Ludovica; Koncan, Raffaella; Misin, Andrea; Toffoli, Barbara; D'Agaro, Pierlanfranco; Luzzati, Roberto; Fabris, Bruno; Bernardi, Stella
Abstract : Purpose . Obesity is a risk factor for severe coronavirus disease 2019 (COVID-19). Circulating adipokines have been associated with inflammatory burden and amplified or dysregulated immune responses. This study aimed to evaluate the discriminatory ability of adipokines to identify COVID-19 pneumonia and to assess disease severity. Methods . We conducted an observational case-control study, with a prospective design, and recruited patients with diagnosis of COVID-19 pneumonia ( n  = 48) and healthy controls ( n  = 36), who were matched by age, sex, and BMI. Leptin, adiponectin, IL-6, and TNF- α were measured by ELISA. Results . Patients with COVID-19 pneumonia had higher levels of leptin, lower adiponectin/leptin (Adpn/Lep) ratio, and higher expression of IL-6. Leptin had an acceptable discriminatory accuracy for COVID-19 pneumonia in patients with BMI >30 (AUC 0.74 [0.58, 0.90]) with a cutoff of 7852 pg/mL and it was associated with maximum respiratory support. By contrast, Adpn/Lep had an excellent discriminatory accuracy for COVID-19 pneumonia in patients with BMI <25 (AUC 0.9 [0.74, 1.06]) with a cutoff of 2.23. Conclusion . Our data indicate that high Adpn/Lep (>2.23) in lean patients is consistent with a state of good health, which decreases in case of inflammatory states, ranging from adipose tissue dysfunction with low-grade inflammation to COVID-19 pneumonia.